Intestinal expression of human apolipoprotein A-IV in transgenic mice fails to influence dietary lipid absorption or feeding behavior. - Aalto-Setälä, K; Bisgaier, C L; Ho, A; Kieft, K A; Traber, M G; Kayden, H J; Ramakrishnan, R; Walsh, A; Essenburg, A D; Breslow, J L (The Journal of Clinical Investigation, 1994)
Two transgenic mouse lines, expressing low or high amounts of human apo A-IV were created. In low and high expressor HuAIVTg mice on a chow diet, serum human apo A-IV levels were 6 and 25 times the normal human level and on a high fat diet, they were 12 and 77 times higher. Human apo A-IV was equally distributed between lipoprotein (mainly HDL) and lipid-free fractions. Intestinal absorption of radiolabeled cholesterol and triglycerides was unaffected in HuAIVTg mice. Vitamin A, carried exclusively in chylomicrons and their remnants, was catabolized normally. When an intragastric vitamin E bolus is given to the HuAIVTg mice, the initial absorption and appearance in triglyceride-rich lipoproteins was similar to that observed in normal mice. However, elevated amounts of vitamin E were subsequently observed in the VLDL of the HuAIVTg mice. Furthermore, in the fed state, serum VLDL triglycerides were markedly elevated in HuAIVTg mice. This effect was greater in high expressor mice. Serum total cholesterol was not elevated, but the distribution was altered in the HuAIVTg mice; VLDL-C was increased at the expense of VLDL-C. Kinetic studies suggested a delayed clearance of VLDL in HuAIVTg mice. Apo A-IV has been suggested to be a satiety factor, but no effect on feeding behavior or weight gain was observed in these HuAIVTg mice. In summary, our studies with HuAIVTg mice show that additional apo A-IV does not effect intestinal absorption of fat and fat-soluble vitamins, and at least chronic elevation of plasma apo A-IV does not effect feeding behavior in this model system. Images